Effectiveness of Utilization of Home Yard Land in Supporting Food Availability in Rural Areas - Rahman, Abdul; Tawe, Amiruddin; Rakib, Muhammad; Sulolipu, Andi Annisa (PT. Maju Malaqbi Makkarana, 2024)
The problem of national food security is something that needs to be addressed sustainably by society and the government, especially in rural areas. To support food availability for the community, land is needed that can be used for food development. One alternative is to use the yard of the house. Home gardens not only function as areas that provide beauty and coolness, but also as productive land that supports national food security by empowering local potential, both in rural and urban areas. Apart from that, the use of the yard also contributes to improving the family's economy. This research aims to examine the characteristics of residents regarding the use of homestead land in rural areas, analyze their utilization patterns, and assess the effectiveness of using homestead land in supporting food availability. The data in this research were analyzed using an experimental method, which involved initial measurements (pre-test), providing treatment in the form of guidance or direction regarding land use, and follow-up measurements (post-test). The research sample was selected using the snowball sampling method, namely a sampling technique based on individual networks. The research results show that the use of yard land is effective in supporting food availability. This is shown by the respondent's answer score on the program effectiveness variable, which is in the range of 50-100%, so it is included in the effective category